Вы находитесь на странице: 1из 8

Three Different Cases:

Case I: No element in the first column is zero.

Case II: A zero in the first column but some other elements of the row

containing the zero in the first column are nonzero.

Case III: A zero in the first column and the other elements of the row

containing the zero are also zero.

Case I: No element in the first column is zero.

Example: Second order system

q( s )  a2 s 2  a1s  a0  0

s2 a2 a0
b1
a a   a2 0   1
 1 0
a2 a0
s1 a1 0 a1 a1 a1 0
s0 b1 0 b1  a0

The requirement for a stable second order system is simply that all the
coefficient be positive or all the coefficient s be negative.
Case II: A zero in the first column but some other elements
of the row containing the zero in the first column are nonzero.

Example:

q(s) = s 5 + 2s 4 + 2s3 + 4s2 +11s +10 = 0

s5 1 2 11
b1 =
( 2) ( 2) - (1) ( 4) = -1
1 2
s 4
2 4 10 2 2 2 4
s 33 be01 6 0 b1 = 0
s2 c1 10 0
s1 d1 0 0 ®e
0 ¾¾
s 0 10 0 0
Case II: A zero in the first column but some other elements
of the row containing the zero in the first column are nonzero.

Example:

q(s) = s 5 + 2s 4 + 2s3 + 4s2 +11s +10 = 0

s 5
c1 =
(e ) ( 4) -12 = -1 2 4
s 5
11 2 2 11 11
e e e 6 4e << 12
s 4s
4
22 4 4 10 10 4e -12 4e » 0
c1 =
s 3 s3 ee 66 0 0 e
s2s
2
-12
c1 1010 0 0
e
s1 s
1
dd11 00 0 0 -12
c1 = sign change!
e
s 0
s 0
10
10 00 0 0
Case II: A zero in the first column but some other elements
of the row containing the zero in the first column are nonzero.

Example:

q(s) = s 5 + 2s 4 + 2s3 + 4s2 +11s +10 = 0

æ -12 ö
ç ÷ ( 6) - (e ) (10) e 6
s 5
1 2 11 è e ø -1
d1 = =
-12 -12 -12
s4 2 4 10 10
e e e
s3 e 6 0 æ -e ö æ 10 ö
d1 = 6 -10e ç ÷ = 6 + e 2 ç ÷
s2 -12 10 0 è 12 ø è 12 ø
e
d1 = 6
s11 d61 0 0

s0 10 0 0 Two sign changes indicates

two poles in the right hand
plan (unstable system)
Case III: A zero in the first column and the other elements of
the row containing the zero are also zero.

Example:

q( s )  s 5  2 s 4  4 s 3  8s 2  3s  6  0
b =
( 2) ( 4) - (1) (8) = -1 1 4
1
ss 55 11 44 33 2 2 2 8
ss 44 22 88 66 b1 = 0

s 33 0 0 0
s b1 b2 0
b2 =
( 2) (3) - (1) ( 6) = -1
1 3
s2 c1 c2 0 2 2 2 6

s1 d1 d2 0 b2 = 0

s0 e3 0 0
Zero row is replaced by an
auxiliary function derived from
preceding non-zero row
Case III: A zero in the first column and the other elements of
the row containing the zero are also zero.

In this example, auxiliary function created from s4 row.

2s 4 +8s2 + 6 = 0 ¾equivalent
¾¾¾ ® s 4 + 4s 2 + 3 = 0

4s +8s = 0 ¾¾¾¾
3
® s + 2s = 0
equivalent 3 2

Auxiliary function is now substituted into third row of array

Case III: A zero in the first column and the other elements of
the row containing the zero are also zero.

Example:

q( s )  s 5  2 s 4  4 s 3  8s 2  3s  6  0

s5 1 4 3
s4 2 8 6
No sign changes in first column of
s3 1 2 0 Routh array indicates system stability
s2 4 6 0
s1 0.5 0 0
s0 6 0 0